2006
DOI: 10.1182/blood-2006-04-014480
|View full text |Cite
|
Sign up to set email alerts
|

Cancer-testis antigens are commonly expressed in multiple myeloma and induce systemic immunity following allogeneic stem cell transplantation

Abstract: Immunotherapies using cancer-testis (CT)antigensin 1 of these patients. These allogeneic immune responses were not detectable in pretransplantation samples and in the patients' stem cell donors, indicating that CT antigens might indeed represent natural targets for graft-versus-myeloma effects. Immune responses induced by alloSCT could be boosted by active CT antigen-specific immunotherapy, which might help to achieve long-lasting remissions in patients with MM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
146
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 151 publications
(153 citation statements)
references
References 47 publications
7
146
0
Order By: Relevance
“…CTA expression in myeloma has been evaluated in large patient sets but emphasis has so far been on newly diagnosed patients. 13,16,29,30 Compared to the study of Condomines et al, 16 presence of gene expression frequency differed no more than 2-fold in 73% of overlapping genes when compared to the frequencies found in newly diagnosed patients in our study. Of these, 12 are highly correlated with a difference in frequency of no more than 1.5-fold, including MAGEC1, MAGEA5 and SSX3; 61%, 26% and 3% in our study and 66%, 22% and 3% in the study of Condomines et al 16 In some cases, different probe sets belonging to the same gene may explain the difference in expression frequencies between the two studies.…”
Section: Discussionmentioning
confidence: 38%
“…CTA expression in myeloma has been evaluated in large patient sets but emphasis has so far been on newly diagnosed patients. 13,16,29,30 Compared to the study of Condomines et al, 16 presence of gene expression frequency differed no more than 2-fold in 73% of overlapping genes when compared to the frequencies found in newly diagnosed patients in our study. Of these, 12 are highly correlated with a difference in frequency of no more than 1.5-fold, including MAGEC1, MAGEA5 and SSX3; 61%, 26% and 3% in our study and 66%, 22% and 3% in the study of Condomines et al 16 In some cases, different probe sets belonging to the same gene may explain the difference in expression frequencies between the two studies.…”
Section: Discussionmentioning
confidence: 38%
“…In an allogenic transplantation setting, Atanackovic et al recently showed that at least four CT Ags expressed by MMC were immunogenic in vivo. Indeed in nine of 35 patients, an allograft resulted in the emergence of anti-SSX2, anti-MAGE-A3, and/or anti-NY-ESO-1 Abs in recipients' sera (59). In the same study, a humoral response against CT Ags was detected in the serum of only one patient of 22 treated with HDC and ABSCT.…”
Section: Discussionmentioning
confidence: 81%
“…First, we selected 20 CT genes characterized by a strictly testis-specific expression and absence from any other healthy tissues as demonstrated in our previous studies [17][18][19]. The expression of these genes was then analyzed in 10 untreated AML cell lines by RT-PCR.…”
Section: Aml Cell Lines Show a Scarce Constitutive Expression Of Ctamentioning
confidence: 99%